Contrast‐Enhanced Ultrasound for the Evaluation of Renal Transplants. (15th May 2020) - Kazmierski, Brittany J.; Sharbidre, Kedar G.; Robbin, Michelle L.; Grant, Edward G.
Abstract : Contrast‐enhanced ultrasound has emerged as a useful imaging modality for the evaluation of the transplant kidney. Advantages over traditional imaging modalities such as computed tomography and magnetic resonance imaging include the ability to visualize a lesion's enhancement pattern in real time, the lack of nephrotoxicity, and relatively low cost. Potential uses of contrast‐enhanced ultrasound include characterization of solid and cystic transplant renal masses, assessment for pyelonephritis and identification of its complications, and evaluation of transplant complications in immediate and delayed settings. Contrast‐enhanced ultrasound will likely play an increasing role for evaluating the transplant kidney, as an accurate diagnosis based on imaging can direct treatment and prevent unnecessary interventions.